2008
DOI: 10.5511/plantbiotechnology.25.447
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis VIP6/ELF8, the homolog of CTR9 component of the transcriptional complex PAF1, is essential for plant development

Abstract: Gene regulation in eukaryotes is affected by chromatin structure. Changes in chromatin structure are regulated by multiple ways of histone modifications, such as acetylation, methylation, and ubiquitination. It is believed that the trimethylated histone H3 at lysine 4 (H3K4), 36 (H3K36) and 79 (H3K79) are hallmarks of active chromatins (Shilatifard 2006). In yeast, trimethylation of H3K4 in the 5Ј region of the target gene is catalyzed by the SET1 histone methyltransferase, and the recruitment of SET1 protein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 40 publications
1
6
0
Order By: Relevance
“…3D ). While the ths1 mutant did not show a clear difference from wild type, vip3-2 , vip5-062223 and null vip6-065364 (elf8-2 ) ( He et al , 2004 ; Oh et al , 2004 ; Shiraya et al , 2008 ) mutants showed a dramatic difference in how their roots responded to growth on hard agar, with a wider range of slanting angles and no preference for slanting direction. In summary, ths1 mutants have defects in root skewing and coiling assays when propyzamide is added, and vip null mutants have defects in root skewing and coiling assays both with and without propyzamide.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…3D ). While the ths1 mutant did not show a clear difference from wild type, vip3-2 , vip5-062223 and null vip6-065364 (elf8-2 ) ( He et al , 2004 ; Oh et al , 2004 ; Shiraya et al , 2008 ) mutants showed a dramatic difference in how their roots responded to growth on hard agar, with a wider range of slanting angles and no preference for slanting direction. In summary, ths1 mutants have defects in root skewing and coiling assays when propyzamide is added, and vip null mutants have defects in root skewing and coiling assays both with and without propyzamide.…”
Section: Resultsmentioning
confidence: 91%
“…The VIP3 protein has been detected both in the Paf1 complex and in the Superkiller (SKI) complex ( Dorcey et al , 2012 ). Several other proteins (VIP4, VIP5, VIP6/ELF8 and VIP2/ELF7) are known to be part of the Paf1 complex but not the SKI complex ( Zhang and van Nocker, 2002 ; Zha ng et al , 2003 ; He et al , 2004 ; Oh et al , 2004 ; Oh et al , 2008 ; Shiraya et al , 2008 ; Park et al , 2010 ). To determine if the touch insensitivity of ths1 can be attributed to the action of the Paf1 complex, we tested null vip5-062223 mutants ( Oh et al , 2004 ) in the paintbrush assay.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that NRF2/ELF8 is a single‐copy gene that is ubiquitously expressed in most plant tissues (He et al ., 2004). The loss of function of ELF8 leads to several growth defects in plants, including male gametophyte development (Shiraya et al ., 2008). In yeast, knockout mutant of the NRF2/ELF8 homolog CTR9 also showed growth defects (Oh et al ., 2004; Marton & Desiderio, 2008; Zhang et al ., 2010; Rodrigues & Lydall, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…New Phytologist including male gametophyte development (Shiraya et al, 2008). In yeast, knockout mutant of the NRF2/ELF8 homolog CTR9 also showed growth defects (Oh et al, 2004;Marton & Desiderio, 2008;Zhang et al, 2010;Rodrigues & Lydall, 2018).…”
Section: Researchmentioning
confidence: 99%
“…Arabidopsis thaliana strain Columbia-0 (Col-0) was used as wild type (WT). The mutant alleles used in this study were: ldl3-1 (GABI_092C03) (Ishihara et al, 2019), elf7-2 (SALK_046605) (Tamada et al, 2009), elf7-3 (SALK_019433) (Cao et al, 2008; Li et al, 2019), elf8-1 (SALK_090130), elf8-2 (SALK_065364) (Shiraya et al, 2008), vip3-1 (SALK_139885) (Fal et al, 2017, 2019), vip4-4 (SALK_039374) (He et al, 2004; Li et al, 2019), vip5-1 (SALK_062223) (Oh et al, 2004), cdc73-1 (SALK_150644) (Yu & Michaels, 2010), cdkf;1-1 (SALK_148336) (Hajheidari et al, 2012), hub1-4 (SALK_122512) (Cao et al, 2008), hub2-2 (SALK_071289) (Cao et al, 2008), sdg8 ( ashh2-1 , SALK065480) (Grini et al, 2009), all of which are in the Col-0 background. Plants were grown on Murashige and Skoog (MS) media supplemented with 1% sucrose and solidified with Bacto agar under long day (16 h light/8 h darkness) photoperiods at 22ºC.…”
Section: Methodsmentioning
confidence: 99%